PRODUCT QUALITY ANALYSIS USING SIX SIGMA METHOD AND FAILURE MODE AND EFFECT ANALYSIS (FMEA) IN FURNITURE PRODUCTS - Arifianto , Muhammad Adi; Sulistiyowati , Wiwik (Journal for Technology and Science, 2024)
PT KKA is an export-oriented rattan furniture industry. In production, product defects often occur due to many factors that have not found a solution to fix them. Based on the results of observations in May, there were 487 units produced with 63 units or 13% returned, June 513 units produced with 57 units or 11% returned, and in July 445 units with 72 units returned. or 16%. This means that for 3 months the value of the reject percentage has increased by 3%. The application of the Six Sigma method is expected to identify and minimize the root causes of defects. FMEA is used to identify potential failures and the effects of failure on a process. The results of the Six Sigma test obtained a DMPO value of 27,590.8. The biggest percentage of defects are loose defects of 39%, and 22% color defects. The results of the FMEA analysis for loose defects have the highest RPN value of 294, this is due to the use of nail guns that are not appropriate and the checking method is only visual, suggestions for improvement are given, namely providing supervision and improving technical checking by moving one by one the joints and selecting materials which exists.